Respostas

2013-11-16T13:24:12-02:00
P.A:{ x - 2r, x - r, x, x+1, x+2}

x -2r + x - r + x + x + r + x + 2r= 65

5x - 3r + 3r = 65
5x = 65
x = 65 / 5
x = 13

x - 2r * x - r = 24
13 - 2r * x - r = 24
169 - 13r - 26r + 2r^2 =24
2r^2 - 39r + 169 - 24 = 0
2r^2 - 39r + 145 = 0

Δ = b² - 4 a c
Δ = 39² - 4 * 2 * 145
Δ = 1521 - 1160
Δ = 361

r = -b ± √Δ / 2.a
r = - ( - 39 ) ± 19 / 4
r = 39 ± 19

r' = 39 + 19 = 58 / 4 = 14,5
r'' = 39 - 19 = 20 / 4 = 5

x - 2r = 13 - 2 * 5 = 13 - 10 = 3
x - r = 13 - 15 = 8
x = 13

x + r = 13 + 5 = 18
x + 2r = 13 + 2 * 5 = 13 + 10 = 23

PA: { 3, 8, 13, 18, 23 }.
1 3 1
Mais tem como responder isso ai so com P.A ?